Fintech Integrated Economic Education Model: Improving Inclusive Financial Competence Among Millennial MSMEs - Farwita, Syurwana; Arsyad, Nursyam; Ibadurrahman, Ibadurrahman; Utomo, Jepri; Mutmainnah, Inayatul (Newinera Publisher, 2025)
This research aims to develop and test a fintech-integrated economic education model to improve inclusive financial competence among millennial MSMEs in Makassar City. Using a descriptive qualitative approach, the study involved ten MSME actors selected purposively and explored their financial behavior, challenges, and responses to a structured training model. The model combines basic economic education, practical use of digital financial applications, and reflective learning processes. Data were collected through interviews, observations, documentation, and pre-test and post-test analysis. The results show significant behavioral changes in financial management, including routine bookkeeping, financial separation between personal and business funds, and improved budgeting practices using fintech tools. The model proves effective in contextualizing economic education and digital literacy within the everyday business practices of MSMEs. These findings underscore the importance of designing participatory, practical, and technology assisted learning models to enhance financial inclusion and empower small business actors sustainably.